Interrelationship between dental clinicians and laboratory technicians: a qualitative study - Ismail, Eman H.; Al-Moghrabi, Dalya (BMC oral health, 2023)
Background Effective communication among members of the dental team is essential for the delivery of high-quality dental care. However, an in-depth understanding of issues concerning the interrelationship between dental clinicians and laboratory technicians has not been previously undertaken. Therefore, the aim of the study was to explore factors influencing the interrelationship between dental clinicians and laboratory technicians. Methods Semi-structured interviews were conducted with dental clinicians and laboratory technicians using purposeful snowball sampling. Two trained researchers conducted the interviews based on a pre-piloted topic guide. The interviews were conducted via video conferencing platform, audio-recorded, and transcribed verbatim. Field notes were taken during the interviews. Framework Methodology was used to analyze the data. Results A total of 20 dental clinicians and laboratory technicians were interviewed. The average interview duration was 37 min. Participants mainly reported negative encounters and highlighted the importance of training and exposure, collaborative learning, and alignment of expectations of both parties in terms of cost of laboratory work, turnaround time, and patient preferences. The relationship between dental clinicians and laboratory technicians depends largely on effective teamwork dynamics and open communication channels. Increased workload, workforce shortage, availability of digital systems, management policies, and financial challenges were emphasized as organizational factors affecting the interrelationship between both groups. Participants highlighted the importance of shadowing, mentorship, education courses, joint discussions, patient-technician rapport, and adoption of digital technology for fostering collaborative practices between the professions. Conclusions A multitude of factors influencing the dental clinician-laboratory interrelationship at individual, interpersonal and organizational levels were identified. This study highlights the need to build a transformative relationship underpinned by mutual trust and respect. Such a collaborative relationship will facilitate optimal patient care and successful treatment outcomes. The outcome of this study can help stakeholders identify solutions for enhancing the interrelationship among the dental team, to ultimately improve patient care and efficiency of dental services.